2019
DOI: 10.3390/ma12162520
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Characterization of Novel LDPE-Based Wear-Resistant Composite Suitable for FDM 3D Printing

Abstract: Low-density polyethylene (LDPE) composites reinforced with finely powdered waste glass were identified as a potential material for 3D printed structures for use in low-duty frictional applications. A recently published 3D printing model was used to calculate the limits in the filament feed rate and printing speed. Tribological tests (pin-on-disc method) of the printed composites were performed for different print-path directions. Differential scanning calorimetry (DSC) was performed on the samples and the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…[ 30 , 31 ]. Using a fine glass powder as reinforcement improved the wear resistance of LDPE-based composites [ 32 ]. The research compared the coefficient of friction of composite materials with those of matrix materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 , 31 ]. Using a fine glass powder as reinforcement improved the wear resistance of LDPE-based composites [ 32 ]. The research compared the coefficient of friction of composite materials with those of matrix materials.…”
Section: Introductionmentioning
confidence: 99%
“…Although ultra-high molecular weight polyethylene (UHMWPE) is primarily utilized in hip prostheses, HDPE exhibits much better processing properties even though it has slightly worse tribological properties. For this reason, HDPE remains a competitive material in this group of applications [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that porcelain composites showed better properties than glass composites for abrasive tools (low wear rate and high hardness), with the best results being obtained for grit size of 150 μm. Olesik et al used glass powder (0–30 wt %) obtained from laminated car glass waste as reinforcement in a low-density PE matrix [ 133 ]. The authors obtained 3D-printed LDPE-based composites with the improved wear resistance resulted from the formation of a sliding film on the composite surface.…”
Section: Postconsumer Waste Materialsmentioning
confidence: 99%